Beyond adoption of shared bike: A case study on antecedents and consequences of brand attachment in Taiwan. (September 2021) - Chen, Ching-Fu; Chen, Yi-Xuan; Mu, Po-Jen; Yu, Yu-Huan
Abstract: The bikesharing studies on user adoption and operational logistics render little understanding of how users' motivation influences their continuous participation in bikesharing services. Drawing on brand attachment theory and perceived value theory, this study proposes and empirically examines an integrated model of interrelationships between perceived value, brand attachment, psychological ownership, and brand citizenship behavior among bikesharing users. Specifically, three dimensions of perceived value including symbolic, functional, and economic values are conceptualized as the antecedents of brand attachment. Using an online survey sample of 462 bikesharing users in Taiwan, our findings indicate that both symbolic and economic values instead of functional value have significant positive effects on brand attachment. We found that psychological ownership mediates between brand attachment and brand citizenship behavior. User's brand attachment leads to positive influence on both psychological ownership and brand citizenship behavior. Psychology ownership also has a positive effect on brand citizenship behavior.